PENGARUH TINGKAT KESEHATAN KEUANGAN, EVA, DAN NILAI KAPITALISASI PASAR TERHADAP RETURN SAHAM - Ardiansyah, Windra; Amanah, Lailatul (Jurnal Ilmu dan Riset Akuntansi (JIRA), 2015)
This research is meant to find out the influence of financial distress potency, Economic Value Added, and market capitalism value to the stock return in LQ 45 which companies which are listed in Indonesia Stock Exchange in 2010-2014 periods. This research is a quantitative research. The samples are 32 companies which are included in the LQ45 index, the observation years is from 2010 to 2014 which has been done by using purposive sampling technique. The analysis technique has been done by using multiple linear regressions with SPSS 18. Based on the result of multiple linear regressions with its significance level is 5% and the result shows that the regression equation of goodness of fit test of has significance level is 0.000 which is smaller than (Î±=0.05), it means that the potency variables i.e. financial distress, Economic Value Added (EVA) and market capitalism value are in accordance with the explanatory variables from the stock return. Hypothesis test, the first hypothesis (H1) and second hypothesis (H2) stated that the potency variables i.e. financial distress and Economic Value Added have positive influence to the stock return. Meanwhile, the third hypothesis (H3) is stated that market capitalism value has positive influence to the stock return but it is denied because the result of hypothesis test shows that market capitalism value has negative influence to the stock return.Keywords: Financial Distress, Economic Value Added, Market Capitalism Value, Stock Return